Quantitative assessment and risk factors for nipple–areolar complex malposition after nipple-sparing mastectomy - Makiguchi, Takaya; Nakamura, Hideharu; Fujii, Takaaki; Yokoo, Satoshi (Breast cancer (Tokyo, Japan), 2019)
Purpose Nipple sparing mastectomy (NSM) for breast cancer preserves the nipple–areola complex (NAC) and has limited the extent of the scar, giving good cosmetic results. However, NAC malposition may occur. The aim of this study is to evaluate NAC malposition after NSM and to determine factors associated with malposition in two-stage reconstruction. Methods The subjects were 46 patients who underwent unilateral NSM, without contralateral mastopexy or reduction surgery, in two-stage reconstruction using an expander with implant or flap replacement. Vertical and horizontal NAC malposition and predictors of malposition were evaluated before and more than 1 year after reconstruction surgery. Results The total amount of saline injected into the expander and aging were significant predictors of increased superior malposition of NAC before and more than 1 year after reconstruction or implant surgery. In contrast, the amount of saline injected into the expander until 2 weeks after expander insertion was a significant predictor of decreased superior NAC malposition. BMI was also a statistically significant predictor of decreased superior NAC malposition, but this result was likely to have been due to the measurement method. Autologous reconstruction was a significant negative predictor of superior malposition at more than 1 year after surgery. Superior NAC malposition resulting from full expansion of the expander improved by a mean vertical angle of 4.5° after autologous reconstruction, but hardly improved after implant use. In autologous reconstruction, NAC tended to move slightly to the lateral side after autologous reconstruction, compared to implant use. Conclusions Until 2 weeks after expander insertion, as much saline as possible should be injected to prevent superior NAC malposition. At full expansion, superior malposition of vertical angle > 4.5° may require repositioning surgery.